Applications of Nanomaterials in Asymmetric Photocatalysis: Recent Progress, Challenges, and Opportunities. Issue 6 (16th July 2020) - Qiu, Xueying; Zhang, Yin; Zhu, Yanfei; Long, Chang; Su, Lina; Liu, Shaoqin; Tang, Zhiyong
Abstract: Asymmetric catalysis is one of the most attractive strategies to obtain important enantiomerically pure chemicals with high quality and production. In addition, thanks to the abundant and sustainable advantages of solar energy, photocatalysis possesses great potential in environmentally benign reactions. Undoubtedly, asymmetric photocatalysis meets the strict demand of modern chemistry: environmentally friendly and energy‐sustainable alternatives. Compared with homogeneous asymmetric photocatalysis, heterogeneous catalysis has features of easy separation, recovery, and reuse merits, thus being cost‐ and time‐effective. Herein, the state‐of‐the‐art progress in asymmetric photocatalysis by heterogeneous nanomaterials is addressed. The discussion comprises two sections based on the type of nanomaterials: typical inorganic semiconductors like TiO2 and quantum dots and emerging porous materials including metal–organic frameworks, porous organic polymers, and organic cages. Finally, the challenges and future developments of heterogeneous asymmetric photocatalysis are proposed. Abstract : Heterogeneous asymmetric photocatalysis well meets the strict demands of the modern chemistry industry and has attracted great interest in recent decades. The state‐of‐the‐art progress in asymmetric photocatalysis by heterogeneous nanomaterials is reviewed. The discussion comprises two sections based on the type of nanomaterials: inorganic semiconductors and porous materials. Finally, challenges and future developments of heterogeneous asymmetric photocatalysis are proposed.